Pengaruh Struktur Tata Kelola Perusahaan dan Efektivitas Komite Audit terhadap Kinerja Keuangan Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia - Aulia Nur Rofiah; Maria Goretti Kentris Indarti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study examines the influence of the proportion of independent directors, CEO duality practices, the proportion of independent commissioners, and the effectiveness of the audit committee on the company's financial performance. The population in this study consists of banking companies listed on the Indonesia Stock Exchange for the 2022-2024 period. There were 42 banking companies that met administrative requirements and were actively listed on the IDX during this period, and the sample used in this study consisted of 42 companies. The analysis technique used in this study is multiple linear regression. The results of the study indicate that independent directors have a negative but insignificant effect on financial performance, CEO duality has a negative but insignificant effect on financial performance, independent commissioners have a negative but insignificant effect on financial performance, the audit committee has a positive but insignificant effect, while leverage has a negative but insignificant effect on financial performance.